The causes and effects of hybrid anti-impunity commissions: Outline of a research agenda - Theresa Reinold (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2020)
In a variety of issue-areas in global governance, hybrid solutions have been experi-ented with in order to address the dilemma created by the export of Western templates of good governance, democracy, the rule of law, etc. to non-Western contexts. The latest manifestation of this global trend towards hybridity are hybrid anti-impunity commissions which have begun to proliferate in Latin America, and which are likely to produce ripple-effects beyond the continent. Their prototype, the Comision Internacional Contra la Impunidad en Guatemala (CICIG), was deployed in Guatemala; later, variants of CICIG were created in Honduras, El Salvador, and Ecuador. However, the new hybrids remain largely underresearched. This contribution therefore discusses the state of art and outlines a research agenda on these new hybrid commissions, arguing that, on the one hand, the effects of these mechanisms require further scrutiny - how do hybrid anti-impunity commissions shape a variety of possible outcomes including the rule of law, statehood, sovereignty, democracy, and the like? On the other hand, we should investigate the factors that contribute to the establishment, successes, and failures of these hybrids, thus treating them as outcomes to be explained. – – In verschiedenen Problembereichen der Global Governance wurden hybride Lösungen erprobt, um dem Dilemma zu begegnen, das durch den Export westlicher Vorlagen für gute Regierungsführung, Demokratie, Rechtsstaatlichkeit usw. in nicht-westliche Kontexte entstanden ist. Die jüngste Manifestation dieses globalen Trends zur Hybridität sind hybride Kommissionen zur Bekämpfung der Straffreiheit, die sich in Lateinamerika auszubreiten begonnen haben und die wahrscheinlich über den Kontinent hinaus Wellen schlagen werden. Ihr Prototyp, die Comision Internacional Contra la Impunidad en Guatemala (CICIG), wurde in Guatemala eingesetzt; später wurden Varianten der CICIG in Honduras, El Salvador und Ecuador geschaffen. Diese neuen Hybriden sind jedoch noch weitgehend unerforscht. In diesem Beitrag wird daher der Stand der Technik erörtert und eine Forschungsagenda zu diesen neuen hybriden Kommissionen skizziert. Dabei wird argumentiert, dass einerseits die Auswirkungen dieser Mechanismen noch genauer untersucht werden müssen - wie gestalten hybride Kommissionen zur Bekämpfung der Straflosigkeit eine Vielzahl möglicher Ergebnisse, darunter Rechtsstaatlichkeit, Staatlichkeit, Souveränität, Demokratie und Ähnliches? Andererseits sollten wir die Faktoren untersuchen, die zur Etablierung, zu Erfolgen und Misserfolgen dieser Hybriden beitragen, und sie so als Resultate behandeln, die einer Erklärung bedürfen.
urn:nbn:de:hbz:464-20201119-103759-7
Keywords: 320; hybridity; anti-impunity commissions; shared-sovereignty arrangements; International Commission against Impunity in Guatemala; Mission to Support the Fight against Corruption and Impunity in Honduras